DESIGN OF A LAN NETWORK DISORDER DIAGNOSTIC SYSTEM WITH A KNOWLEDGE-BASED SYSTEM USING THE FORWARD CHAINING METHOD(CASE STUDY: STAR ENERGY GEOTHERMAL DARAJAT II, LIMITED) - Budiman, Tedi; Abdul Rohmat, Sumpena (RISTEC : Research in Information Systems and Technology, 2022)
Lack of knowledge about LAN network can be overcome by an expert with his knowledge and experiences. Expert systems are developed together with the existence of the information technology. The development of expert systems is aimed as aid facilities to provide solutions in our lives. This expert system can help technicians to get solutions quickly and can save the time. Expert systems use computer technology to integrate, manipulate and display information or features. Expert systems can also help in taking better solutions. This system uses forward chaining method which is the inference method using logical reason that is started from the previous fact to examine the validity of hypotheses. This system is created using JAVA Netbeans program and database using MySQL. This system is provided an expert menu for knowledge management, so the expert can add, change and delete the knowledge. This system uses UML (Unified Modeling Language) modeling.